Pengaruh Kompetensi Eksekutif, Ukuran Perusahaan, Komisaris Independen, dan Kepemilikan Institusional Terhadap Tax Avoidance - Merslythalia, Retta; Lasmana, Mienati Somya (Jurnal Ilmiah Akuntansi dan Bisnis, 2017)
This research aims to examine the effect of executive competency, the firm size, the independent commissioner and the institutional ownership towards tax avoidance. The number of population in this research is 141 manufacturing companies which are listed in Indonesia Stock Exchange during 2012 to2014. This research uses purposive sampling technique. The multiple linear regression analysis is used to analyze the data. There are 49 companies used as the samples of this study. Based on the conducted data analysis on this research, it concludes that:( 1 ) the executive competence has no effects on tax avoidance ( 2 ) the firm size has no effects on tax avoidance ( 3 ) the independent commissioner has no effects on tax avoidance while ( 4 )the institutional ownership affects tax avoidance.
Keywords: executive competence, firm size , independent commissioner , ownership of institutional , tax avoidance